In vitro and in vivo comparison of eravacycline- and tigecycline-based combination therapies for tigecycline-resistant Acinetobacter baumannii. (3rd April 2022) - Yin, Ti; Lai, Jiun-Ji; Huang, Wei-Cheng; Kuo, Shu-Chen; Chiang, Tsung-Ta; Yang, Ya-Sung; ,
Abstract: Several antimicrobial combination therapies are used to treat multiple drug resistant (MDR) and extensively drug resistant (XDR) Acinetobacter baumannii infections. A novel antibiotic, eravacycline, shows a higher potency than tigecycline. The efficacies of eravacycline-based therapies have not yet been evaluated. We demonstrated the effectiveness of eravacycline- and tigecycline-based combination therapies in XDR and especially tigecycline resistant A. baumannii . Thirteen eligible isolates were selected from 642 non-duplicate Acinetobacter blood isolates from four medical centres in 2010–2014. Tigecycline/imipenem and eravacycline/imipenem combinations were simultaneously effective against some isolates in vitro with fractional inhibitory concentration index of 0.5. In contrast, eravacycline- and tigecycline-based combination therapies provided no additional benefits in mouse survival compared to those for monotherapy. In summary, colistin is still the final resort for XDR- A. baumannii treatment according to the sensitivities. Owning to rapid development of resistance in A. baumannii, novel antibiotics are urgently needed.